Pengaruh Keadilan Organisasi Terhadap Etika Kerja Islam: Studi Pada Baitul Mal Wat Tamwil (BMT) Di Kudus - Wahibur Rokhman (Unisia, 2011)
This research is about the influence of organizational justice toward islamic work ethic in Baitul Mat wat Tamwil (BMT) at Kabupaten Kudus. In this research, organizational Justice is measured by three dimension of justice developed by Cropanzano etc (2007), namely distributive justice, procedural justice, and interactional justice. This research also examines the influence of those three dimension of justice toward islamic work ethic felt by the employee. The result of this research showed that the level of organizational justice and islamic work ethic felt by employee in BMT at Kabupaten Kudus is guite high. The result of regression analysis also showed that the influence of distributive justice, procedural justice, and interactional justice toward islamic work ethic are positive and significance.Kata Kunci; Keadilan distribusi, keadilan prosedural, keadilan interaksional dan Etika kerja islam.